Dual-objective optimization strategy of self-adaptive transient pressure controller in water delivery engineering - Boran Zhang; Wuyi Wan; Yuhang Wang; Qihua Ran; Xiaoyi Chen; Yue Fang; Saiyu Yuan; Huiming Zhang (Engineering Applications of Computational Fluid Mechanics, 2024)
Controlling pressure impact of water hammer is an important guarantee for safe and stable running of pipeline systems. Previously, we proposed a spring self-adaptive auxiliary control (SAC) system to improve the pressure control ability of a surge tank. However, the working efficiency of the SAC system is affected by various parameters. A reasonable designing strategy becomes an urgent need to properly determine the parameters of the SAC controller. In this study, based on our calibrated numerical model, various transient responses of a SAC system with different parameters were further investigated. The latency response threshold and the spring orifice coefficient were identified to be the two most sensitive parameters that determine the controller working efficiency. Based on the objectives of reducing the in-pipe extreme pressure and in-tank water level fluctuation, an analytical dual-objective optimizing Method was proposed for application. The results demonstrated that the pressure control capability of SAC controller can be optimized by the proposed method.